(untitled) (International Journal of Engineering and Computer Science, 2015)
In this work an attempt has been made to evaluate the microstructural and wear characteristics of spray formed Al-10Si-20Pb, Al-10Si-20Sn and Al-20Sn alloys. The spray forming method was employed for preparation of samples. The microstructural futures of spray formed alloys were studied under optical microscope. The microstructure of alloys shows uniform distribution of lead and tin particles along the grain boundary of base alloy. The wear characteristics of alloys were investigated under dray sliding condition by pin on disc type wear testing machine. Also the influence of applied load, sliding speed and frictional coefficient are determined. Worn out surface of pins are studied under optical microscope to determine the type of wear mechanism. The wear test results of all alloys shows increase in wear rate with applied load and sliding speed. The spray formed Al-10Si-20Pb alloy exhibits better wear resistance and lower coefficient of friction as compared to Al-10Si-20Sn and al-20Sn alloy